Frost Hazard Assessment on Agricultural Land to Achieve Resilient Agriculture in Dieng Volcanic Highland, Central Java - Aditya Pradana; Aida Mardiana; Fathimah Nur Lestari; Futuha Helen Sara; Sani Afifah; Emilya Nurjani (Jurnal Ilmu Pertanian, 2018)
Dieng Volcanic Highland is one of the most intensive potato agricultural land in Indonesia, as well as frost disaster prone area. Frost indicated by appearance of frozen dew on the ground or vegetation surface due to cold temperatures during dry season. Frost causes damage to leaf tissue in potato plants, resulting crop failure and losses of up to tens of millions. Disaster management needs to be assess in order to achieve Disaster Risk Reduction (DRR) on agricultural land. This research aims to identify frost hazard areas based on local physical characteristics, analyze frost impacts on agricultural land, and provide preparedness recommendation to reduce the impact of frost disasters in Dieng Volcanic Highland. Research was conducted in Dieng Village, Wonosobo and Dieng Kulon Village, Banjarnegara. Method to assess hazard level was performed by spatial mapping technology using ArcGIS and comprehensive analysis using frost assessment through combinations of geomorphology, land use, proximity to water bodies and weather aspects. Dieng Volcanic Highland has a 125.59 hectare frost hazard areas, as many as 58.4 hectares of hazard areas are dominated by high level, while 24.84 hectares are moderate level and 42.95 hectares are low level. Cropland dominated by potato commodity has the highest hazard level, frost incident causing agricultural commodities to wither to death so that farmers experience losses. Frost losses in Dieng have a range from 800 thousand rupiah to over 155 million rupiah and only destructive on potato farm. In order to encourage agricultural resilience and reduce the loss of frost disasters, effort of preparedness can be done by passively and actively methods. Passive methods includes site selection, early warning system, shifting commodities, cropland modification, and appropriate calendar planting. Active methods includes frost modification using heaters, blower and sprinkle irrigation, and cropland covering using mulch, plastic or nets.